Existence of Solutions for p-Kirchhoff Problem of Brézis-Nirenberg Type with Singular Terms - Atika Matallah; Hayat Benchira; M. El Mokhtar Ould El Mokhtar (Journal of Function Spaces)
In this paper, we prove the existence of positive solution for a p-Kirchhoff problem of Brézis-Nirenberg type with singular terms, nonlocal term, and the Caffarelli-Kohn-Nirenberg exponent by using variational methods, concentration compactness, and maximum principle.